High-strength and high-conductivity cement-based composite material and preparation method thereof
By adding iron-based amorphous alloy powder, oyster shell particles and conductive basalt fibers to cement-based composites, the problem of alkali return and low strength of thermoelectric cement-based composites is solved, and the high strength, high toughness and high quality of the material are achieved Thermal conductivity.
Patent Information
- Application Number
- CN202411409536.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-07
AI Technical Summary
The existing thermoelectric cement-based composite materials produce toxic gases, alkali reflux phenomena and low strength when heated, which limits their application scenarios.
By adding iron-based amorphous alloy powder and oyster shell particles to the calcium aluminate cement base, the alkali return phenomenon is suppressed in concert, and the conductive channel is formed through the bridge between conductive basalt fibers and iron-based amorphous alloy powder. Conductive thermal conductivity.
It effectively inhibits the alkali return phenomenon of cement-based composite materials, and at the same time improves its strength, toughness and thermal conductivity, expanding its application scenarios.
Smart Images

Figure CN119390414A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of inorganic non-metallic materials, and more specifically, relates to a high-strength and high-conductivity cement-based composite material and a preparation method thereof. Background Art
[0002] Cement-based materials have high strength, corrosion resistance and durability when used at room temperature. Adding different proportions of conductive materials, such as carbon fiber and carbon black, to cement colloid can greatly improve the thermoelectric properties of the material. The resulting thermoelectric cement-based composite materials are used in wall and roof insulation, thermoelectric deicing pavement and thermoelectric conversion devices for renewable energy. However, thermoelectric cement-based composite materials still have the following problems: (1) When the carbon fiber and carbon black reinforcement materials are heated in the cement matrix, the following reactions occur:
[0003] C+H2O(g)=CO+H2, which produces toxic gas and escapes to the outside, causing the cement colloid to crack or even fall off. (2) Cement colloid will experience alkali reversion during daily use, which will cause it to appear white frost. White frost is calcium hydroxide produced by cement hydration. As water migrates from the inside to the surface, water evaporates and calcium hydroxide crystals precipitate to form white spots. The appearance of white spots not only affects the appearance of the product, but also has trace toxicity. (3) Cement colloid is brittle and has low strength, making it difficult to form thin-walled products, which limits the use scenarios of thermoelectric cement-based composite materials. Summary of the invention
[0004] In order to solve the above-mentioned defects of the prior art, the primary purpose of the present invention is to provide a cement-based composite material which inhibits its alkali reversion phenomenon and improves its strength, toughness and thermal and electrical conductivity.
[0005] Another object of the present invention is to provide a method for preparing a cement-based composite material.
[0006] Another object of the present invention is to provide an application of the cement-based composite material.
[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0008] A cement-based composite material comprises the following raw materials in parts by weight: 300-550 parts of calcium aluminate cement powder, 600-1600 parts of silica sand, 45-160 parts of oyster shell particles, 45-160 parts of iron-based amorphous alloy powder, 5-15 parts of conductive basalt fibers, and 120-280 parts of water.
[0009] The present invention adds iron-based amorphous alloy powder and oyster shell particles to the calcium aluminate cement base to synergistically inhibit the occurrence of alkali reversion. At the same time, the iron-based amorphous alloy acts as a conductive node to bridge the conductive basalt fiber added to the calcium aluminate cement base, so that the conductive fiber and the conductive particles contact each other to form a conductive channel, which greatly improves the electrical and thermal conductivity of the cement base. In addition, the addition of conductive basalt fibers can also effectively improve the toughness and strength of the cement base. Therefore, oyster shell particles, iron-based amorphous alloy powder and conductive basalt fibers are added to the cement-based composite material at the same time. The synergistic effect of the three can inhibit the alkali reversion of the cement-based composite material while improving its strength, toughness, thermal and electrical conductivity.
[0010] Preferably, the cement-based composite material comprises the following raw materials in parts by weight: 400-500 parts of calcium aluminate cement powder, 900-1500 parts of silica sand, 60-120 parts of oyster shell particles, 60-120 parts of iron-based amorphous alloy powder, 8-12 parts of conductive basalt fibers, and 140-250 parts of water.
[0011] Preferably, the particle size of the oyster shell particles is 60 to 500 μm.
[0012] Oyster shell particles are bioceramic composite materials composed of inorganic aragonite fibers and organic collagen. The main component is biological CaCO3, which has high activity. It mixes with water molecules to generate Ca(HCO3)2. Ca(HCO3)2 can react with (OH) formed during cement hydration reaction. - ) reaction to form more stable CaCO3 and calcium aluminosilicate gel or calcium silicate, thereby suppressing the alkaline substances produced during the application of calcium aluminate cement-based composite materials. The specific reaction process is as follows:
[0013] Ca(HCO3)2+Ca2(SiO3)(OH)2→2CaCO3+CaSiO3+2H2O,
[0014] Ca(HCO3)2+Ca2Al2SiO6(OH)2→2CaCO3+CaAl2SiO6+2H2O.
[0015] Preferably, the alloy of the iron-based amorphous alloy powder is selected from one or more of amorphous Fe-Si-B alloy, amorphous Fe-B alloy, amorphous Fe-BC alloy, amorphous Fe-Si-BC alloy, and amorphous Fe-Co-Si-B alloy.
[0016] Preferably, the particle size of the iron-based amorphous alloy powder is 1 to 80 μm.
[0017] The present invention adds iron-based amorphous alloy powder instead of crystalline iron powder to the cement-based composite material because amorphous iron, as a metallic glass, has a higher Gibbs free energy during oxidation due to its long-range disordered atomic structure and thermodynamic non-equilibrium state, and is more likely to produce the following chemical reaction: Fe-2e→Fe 2+ ;Fe 2+ +H2O→FeOH + +H + , amorphous iron reacts to form more H + , which is beneficial to neutralize the alkali produced by cement hydration, thereby inhibiting the alkali return phenomenon during the application of calcium aluminate cement-based composite materials. In addition, the addition of iron-based amorphous alloy powder is beneficial to improving the electrical and thermal conductivity of cement-based composite materials.
[0018] Preferably, the conductive basalt fiber is a basalt fiber with a metal coating on the surface.
[0019] Since the iron-based amorphous alloy particles in the cement-based composite material are dispersed, no connection channel for electron migration is formed, so the iron-based amorphous alloy has limited improvement on the electrical and thermal conductivity of the cement-based composite material. The present invention uses conductive basalt fibers to achieve bridging, so that the conductive fibers and the iron-based amorphous alloy particles contact each other to form a conductive channel, which greatly improves the electrical and thermal conductivity of the cement matrix. The electrical and thermal conductivity mechanism is as follows: Figure 1 As shown, Figure 1 (a) is the iron-based amorphous alloy particles doped in the cement-based composite material. Since the calcium aluminate cement matrix has no conductivity, although the particle conductive filler (iron-based amorphous alloy) has a certain conductivity, they are discretely distributed in the cement-based composite material. The "channel" for electron migration is not really connected, and the whole material is still in an insulating state, so its electrical and thermal conductivity is poor; Figure 1 (b) Conductive basalt fibers are doped into cement-based composite materials. Since the fibers are short in length, they cannot penetrate the entire cement matrix. The entire material is still in an intermittent loop state, so its electrical and thermal conductivity is still not improved. Figure 1(c) is the co-doping of iron-based amorphous alloy particles and conductive basalt fibers, so that most areas of the entire material are in a linked loop state, so the electrical conductivity and thermal conductivity of the cement-based composite material prepared by the present invention is greatly improved under the synergistic effect of the iron-based amorphous alloy and the conductive basalt fibers. In addition, the main components of basalt fibers are SiO2, Al2O3, and ZrO2. When the cement-based composite material is subjected to an external load, the strength at this location will inevitably be reduced due to the appearance of holes, and the holes become a high-risk area for fracture, but the high-strength, high-toughness, and high-modulus fibers can withstand external loads and can bridge between the crack surfaces that are about to be disconnected. The bridged fibers generate a force on the matrix to close the cracks, consume the work done by the external load, and prevent the cracks from opening further. Therefore, the addition of conductive basalt fibers in the present invention can improve the strength and toughness of the cement-based composite material to a certain extent. In addition, the present invention uses basalt fiber to plate conductive metal. Since the composition of basalt itself is very close to that of cement-based components, the affinity between them is relatively large. After metal plating, the partial area that is not plated with metal still maintains a strong bonding force with the cement-based.
[0020] Preferably, the metal plating layer comprises silver and / or nickel metal plating layer.
[0021] More preferably, the metal plating layer is a silver plating layer.
[0022] Preferably, the method for preparing the conductive basalt fiber comprises the following steps:
[0023] S1. Place the basalt fiber in the pretreatment solution and perform ultrasonic vibration for 20 to 30 minutes;
[0024] S2. placing the basalt fiber obtained in step S1 in a chemical plating solution for surface chemical metal plating for 10 to 20 minutes.
[0025] In the present invention, the basalt fiber used may be commercially available basalt fiber having a length of 5 to 35 mm and a radius of 4 to 6 μm.
[0026] In some specific embodiments of the present invention, the method for preparing basalt fiber containing a silver-plated layer on the surface is as follows:
[0027] S1. Pretreatment: placing the basalt fiber in a pretreatment solution for ultrasonic oscillation for 20 to 30 minutes, wherein the pretreatment solution comprises the following components: 0.1 to 0.3 g / L hydroxyethyl cellulose, 3 to 5 g / L sodium citrate, 3 to 5 g / L nickel salt, 0.5 to 2 g / L potassium borohydride, and 5 to 20% mass fraction of sodium hydroxide solution, wherein the components are mixed in a volume ratio of 1:1; the pH value of the treatment solution is 9.5 to 10.5.
[0028] S2. Chemical silver plating: placing the basalt fiber obtained in step S1 in a chemical silver plating solution for chemical silver plating for 10 to 20 minutes, wherein the chemical silver plating solution comprises the following components: 7 to 9 g / L silver nitrate, ammonia water, 5 to 20% mass fraction of sodium hydroxide solution, 9 to 11 g / L glucose, and 80 ml / L anhydrous ethanol, wherein the components are mixed in a volume ratio of 1:1, and the pH value of the chemical silver plating solution is 10.5 to 11.5.
[0029] Preferably, the particle size of the silica sand is 0.2 mm to 3.35 mm.
[0030] The particle sizes of the silica sand, oyster shell particles and iron-based amorphous alloy powder of the present invention form a well-graded continuous fine aggregate, which can fully fill the pores of the cement-based composite material, reduce the void ratio of the cement-based composite material, improve its density, and thus improve its strength.
[0031] Preferably, the chemical components of the calcium aluminate cement powder include calcium aluminate, calcium aluminosilicate, calcium silicate and silicon dioxide.
[0032] The present invention also provides a method for preparing the cement-based composite material, comprising the following steps: mixing water and calcium aluminate cement powder, then adding silica sand, oyster shell particles, iron-based amorphous alloy powder, and conductive basalt fiber and stirring to form mortar, placing the mortar in a mold and vibrating it on a concrete vibration table to obtain the cement-based composite material.
[0033] Preferably, the stirring is carried out using a planetary mixer.
[0034] Preferably, the stirring time is 0.5 to 1 min.
[0035] Preferably, the vibration time is 1 to 3 minutes.
[0036] Preferably, the cement-based composite material is placed in a curing box at 20° C. and a relative humidity of not less than 90% for curing after demoulding.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] The present invention adds iron-based amorphous alloy particles, conductive basalt fibers, oyster shell particles, and silica sand into cement-based composite materials to synergistically improve the electrical and thermal conductivity, inhibit alkali reversion, and enhance strength and toughness of the cement-based composite materials. The cement-based composite materials can be widely used in thermal insulation building materials or thermoelectric conversion device materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1Schematic diagram of the electrical and thermal conductivity mechanism of cement-based composite materials. 1 is the calcium aluminate cement matrix, 2 is the iron-based amorphous alloy conductive particle filler, and 3 is the conductive basalt fiber filler.
[0040] Figure 2 This is the XRD spectrum of calcium aluminate cement powder phase analysis.
[0041] Figure 3 This is the SEM image of the microstructure of oyster shell particles.
[0042] Figure 4 This is the XRD spectrum of the phase composition of oyster shell particles.
[0043] Figure 5 (a) SEM image and (b) EDS element analysis diagram of amorphous Fe-Si-B alloy powder raw material.
[0044] Figure 6 This is the XRD spectrum of amorphous Fe-Si-B alloy powder raw material.
[0045] Figure 7 (a) Microscopic morphology, (b) EDS spectrum and (c) EDS elemental analysis of conductive basalt fiber.
[0046] Figure 8 (a) Microscopic morphology, (b) EDS spectrum and (c) EDS elemental analysis of basalt fiber.
[0047] Fig. 9 This is the XRD pattern of crystalline Fe-Si-B alloy powder.
[0048] Fig.10 This is the XRD spectrum of the phase analysis of the cement-based composite materials of Comparative Example 6, Comparative Example 4, Comparative Example 7 and Example 8 after curing for 28 days.
[0049] Fig.11 These are (a) the microscopic morphology of iron powder, (b) the EDS spectrum and (c) the EDS elemental analysis diagram of the cement-based composite material in Example 8 after 28 days of curing.
[0050] Fig.12 This is a microscopic morphology of the cement-based composite material obtained in Comparative Example 9.
[0051] Fig.13 This is a microscopic morphology of the cement-based composite material obtained in Example 8.
[0052] Fig.14 The effect of oyster shell particles on the pH of concrete simulation fluid.
[0053] Fig.15 This is the effect of iron-based amorphous alloy on the pH value of concrete simulation fluid.
[0054] Fig.16 This is the Evans polarization diagram. DETAILED DESCRIPTION
[0055] The content of the present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present embodiment are conventional reagents, methods and equipment in the art.
[0056] The raw material information for preparing the cement-based composite material used in the examples and comparative examples of the present invention is as follows:
[0057] Calcium aluminate cement powder is commercially available and its ingredients are as follows Figure 2 As shown in the XRD diagram;
[0058] Oyster shell particles were purchased from Nanjing Tong Ren Tang, with a particle size of 60 to 500 μm and a microscopic morphology of Figure 3 As shown, the ingredients are Figure 4 As shown in the XRD pattern;
[0059] The iron-based amorphous alloy powder is amorphous Fe-Si-B alloy powder purchased from Qinghe County Qiqi Metal Company, with a particle size of 1 to 80 μm. Its SEM and EDS element analysis are as follows: Figure 5 As shown, the XRD spectrum is Figure 6 shown.
[0060] The silica sand is commercially available from Huizhi Water Purification Co., Ltd., and its particle size is 0.2 mm to 3.35 mm.
[0061] The preparation method of conductive basalt fiber comprises the following steps: (1) pretreatment: placing basalt fiber in a pretreatment solution, wherein the pretreatment solution is formulated by volume as follows: 1 part of 0.2 g / L hydroxyethyl cellulose, 1 part of 4 g / L sodium citrate, 1 part of 4 g / L nickel salt, 1 part of 1 g / L potassium borohydride, 1 part of 10% mass fraction sodium hydroxide, the temperature is 25°C, the pH value is 10, and ultrasonic oscillation is applied for 20 to 30 minutes. (2) chemical silver plating: placing the basalt fiber obtained by pretreatment in a silver plating solution, and the silver plating time of the basalt fiber is controlled within 10 to 20 minutes. After the silver plating is completed, filtering, repeatedly washing with clean water to obtain a surface-silvered conductive basalt fiber, and drying for standby use. The silver plating solution comprises: 1 part of 8 g / L silver nitrate, 1 part of 10 mL ammonia water, 1 part of 10% mass fraction sodium hydroxide solution, 1 part of 10 g / L glucose, 1 part of 80 ml / L anhydrous ethanol, and the pH value is 11. Its microscopic appearance is Figure 7As shown in the figure, we can see that the white small particles are plated on the fiber surface. The point energy spectrum of the basalt fiber wrapped with silver coating shows that the main component element is silver. The basalt fiber used to prepare the conductive basalt fiber is commercially available from Haining Kenanjie Composite Materials Co., Ltd. Its main components are SiO2, Al2O3, ZrO2, with a length of 5 to 35 mm and a radius of 4 to 6 μm. Its SEM and EDS element analysis are shown in the figure. Figure 8 shown.
[0062] Example 1
[0063] This embodiment provides a cement-based composite material, and the weight proportions of the raw materials used are shown in Table 1.
[0064] The preparation method of the above-mentioned cement-based composite material comprises the following steps: (1) first add water into a stirring pot according to the weight parts in Table 1, then add cement, use a planetary mixer to stir at a low speed for 0.5 to 1 minute, then add silica sand, oyster shell particles, iron-based amorphous alloy powder, and conductive basalt fiber, and use a planetary mixer to stir at a high speed for 0.5 to 1 minute to form a mortar state. (2) Put the mortar into a mold and vibrate it on a vibration table for 1 to 3 minutes. (3) After standing for 24 hours, demould, and place the specimen in a curing box at 20°C and a relative humidity of not less than 90% for more than 7 days to obtain the cement-based composite material.
[0065] Embodiment 2 to Embodiment 8
[0066] The weight parts of the raw materials used in Examples 2 to 8 are shown in Table 1.
[0067] The preparation steps of Examples 2 to 8 are the same as those of Example 1.
[0068] Comparative Example 1
[0069] This comparative example provides a cement-based composite material, which is different from Example 8 only in that the raw materials used do not contain oyster shell particles, and the other raw material components are shown in Table 1.
[0070] Comparative Example 2
[0071] This comparative example provides a cement-based composite material, which is different from Example 8 only in that the raw materials used do not contain amorphous Fe-Si-B alloy powder, and the other raw material components are shown in Table 1.
[0072] Comparative Example 3
[0073] This comparative example provides a cement-based composite material, which is different from Example 8 only in that the raw materials used do not contain conductive basalt fibers, and the other raw material components are shown in Table 1.
[0074] Comparative Example 4
[0075] This comparative example provides a cement-based composite material, which is different from Example 8 only in that the raw materials used do not contain amorphous Fe-Si-B alloy powder and conductive basalt fiber, and the other raw material components are shown in Table 1.
[0076] Comparative Example 5
[0077] This comparative example provides a cement-based composite material, which is different from Example 8 only in that the raw materials used are basalt fibers before silver plating instead of the conductive basalt fibers obtained after silver plating.
[0078] Comparative Example 6
[0079] This comparative example provides a cement-based composite material, which is different from Example 8 only in that the raw materials used do not contain amorphous Fe-Si-B alloy powder, conductive basalt fiber, and oyster shell particles, and the remaining raw material components are shown in Table 1.
[0080] Comparative Example 7
[0081] This comparative example provides a cement-based composite material, which is different from Example 8 only in that the raw materials used do not contain conductive basalt fibers and oyster shell particles, and the other raw material components are shown in Table 1.
[0082] Comparative Example 8
[0083] This comparative example provides a cement-based composite material, which differs from Example 8 only in that a crystalline Fe-Si-B alloy powder with the same composition is used in the raw materials instead of the amorphous Fe-Si-B alloy powder, wherein the crystalline Fe-Si-B alloy powder is prepared by heating the amorphous Fe-Si-B alloy powder used in the present invention to 720-750° C. and cooling it in the furnace. The XRD spectrum of the crystalline Fe-Si-B alloy powder is as follows: Fig. 9 shown.
[0084] Comparative Example 9
[0085] This comparative example provides a cement-based composite material, which is different from Example 8 only in that the raw materials used do not contain amorphous Fe-Si-B alloy powder and oyster shell particles, and the other raw material components are shown in Table 1.
[0086] Table 1
[0087]
[0088]
[0089] Performance Testing
[0090] Thermal diffusion coefficient test: The thermal diffusion coefficient of the cement-based composite materials prepared in the embodiment and the comparative example after curing for 7 days and 28 days was measured using a thermal conductivity instrument LFA447. The results are shown in Table 2.
[0091] Compression and flexural strength test: The compression and flexural strength of the cement-based composite materials prepared in the embodiment and the comparative example after curing for 7 days and 28 days were tested by the GB / T17671-2021 cement mortar strength test method. Six parallel tests were set up, and the average strength value was taken after measurement. The results are shown in Table 2.
[0092] Resistance test: DEMP1 multimeter was used to test the resistance of the cement-based composite materials prepared in the embodiment and the comparative example after curing for 7 days and 28 days. The results are shown in Table 2.
[0093] Phase analysis: The phase composition and crystal structure of the cement-based composite materials prepared in Example 8, Comparative Example 4, Comparative Example 6 and Comparative Example 7 after curing for 28 days were analyzed using UItimaⅢX-ray diffractometer. The detection angle range was 20-80°. The results are shown in the figure. Fig.10 As shown; the phase composition of the cement-based composite materials obtained in the embodiments and comparative examples after curing for 7 days and 28 days was analyzed to see whether alkaline phases (Ca2Al2SiO6(OH)2, Ca2(SiO3)(OH)2) appeared in the XRD spectrum. The results are shown in Table 2.
[0094] Morphology and elemental composition analysis: The microscopic morphology of the raw materials used in the present invention and the cement-based composite materials prepared in the embodiments and comparative examples was analyzed using a German Sigma500 scanning electron microscope and an energy dispersive spectrometer. The results are shown in the figure. Figure 3 (oyster shell particles), Figure 5 (amorphous Fe-Si-B alloy powder), Figure 7 (Conductive basalt fiber), Figure 8 (basalt fiber), Fig.11 (Cement-based composite material obtained in Example 8), Fig.12 (Cement-based composite material obtained in Comparative Example 9) and Fig.13 (Cement-based composite material obtained in Example 8) is shown.
[0095] Table 2
[0096]
[0097] As can be seen from Table 2, the compressive strength of the cement-based composite materials of Examples 1 to 8 after curing for 7 days is greater than 40 MPa, and the compressive strength after 28 days is greater than 55 MPa. The flexural strength after curing for 7 days is greater than 10 MPa, and the flexural strength after curing for 28 days is greater than 12 MPa. The thermal diffusion coefficients of Examples 1 to 8 at 25°C are all greater than 2.0 mm 2 / s, greater than 4.5mm at 250℃ 2 / s; the resistance of the cement-based composite materials after curing for 7 days was less than 40KΩ.cm, and the resistance of the cement-based composite materials after curing for 28 days was less than 30KΩ.cm. Among them, the cement-based composite materials obtained in Example 8 had the best mechanical properties and excellent electrical and thermal conductivity. After the cement-based composite materials of Examples 1 to 8 were cured for 7 days and 28 days, XRD detection showed that no diffraction peaks of alkaline substances Ca2Al2SiO6(OH)2 and Ca2(SiO3)(OH)2 appeared.
[0098] It can be seen from Comparative Examples 1 and 2 that when oyster shell particles or iron-based amorphous alloy particles are doped alone in cement-based composite materials, alkaline phases Ca2Al2SiO6(OH)2 and Ca2(SiO3)(OH)2 are still present. Therefore, the effect of adding oyster shell particles or iron-based amorphous alloy particles alone on inhibiting the alkali reversion phenomenon is not obvious. It can be seen from the data in the examples that under the joint action of oyster shell particles and iron-based amorphous alloy particles, no alkaline phases Ca2Al2SiO6(OH)2 and Ca2(SiO3)(OH)2 exist, indicating that the synergistic effect of the two can effectively inhibit the precipitation of these two alkaline substances, and the effect of inhibiting the alkali reversion phenomenon is significant.
[0099] It can be seen from Comparative Examples 3 and 4 that adding iron-based amorphous alloy powder to cement-based composite materials is beneficial to improving the electrical conductivity and thermal conductivity, but the addition of iron-based amorphous alloy powder alone has limited improvement on the electrical conductivity and thermal conductivity of cement-based composite materials. It can be seen from Comparative Examples 2 and 4 that adding conductive basalt fibers to cement-based composite materials is beneficial to improving the electrical conductivity and thermal conductivity, but the addition of conductive basalt fibers alone has limited improvement on the electrical conductivity and thermal conductivity of cement-based composite materials. It can be seen from Comparative Examples 2, 3 and Example 8 that the synergistic effect of iron-based amorphous alloy particles and conductive basalt fibers can significantly improve the electrical conductivity and thermal conductivity of cement-based composite materials.
[0100] By comparing Comparative Example 5 with Example 8, basalt fibers are added to the cement-based composite material, but the basalt fibers are not silver-plated. It can be seen that the strength of the composite material is close to that of the composite material with the addition of conductive basalt fibers, but the electrical and thermal conductivity is very poor. The main reason is that the main components of basalt fibers are SiO2, Al2O3 and ZrO2, which are all inorganic minerals and can effectively improve the strength of the cement matrix, but they themselves are not conductive. If they are not silver-plated, their electrical and thermal conductivity is still low.
[0101] Comparing Comparative Example 6 with Example 8, only calcium aluminate cement + silica sand + water without any filler is added, and its compressive strength, flexural strength and thermoelectric performance are poor.
[0102] Compared with Example 8, when Comparative Example 7 does not contain oyster shell particles or conductive basalt fibers and only adds iron-based amorphous alloy powder, its compressive and flexural strength properties are poor, and the improvement of electrical and thermal conductivity and performance is limited. In addition, alkaline substances are still present in the XRD spectrum, and the alkali reversion phenomenon cannot be effectively suppressed.
[0103] Comparing Example 8 with Example 8, annealed iron-based crystalline alloy powder is used instead of iron-based amorphous alloy powder. Its compressive strength, flexural strength and thermoelectric properties are close to those of Example 8, and both strength and thermoelectric properties are excellent, but alkaline substances are still present in the XRD spectrum.
[0104] Compared with Example 8, the cement-based composite material does not contain oyster shell particles and iron-based amorphous alloy particles, and only contains one kind of aggregate, silica sand, and fails to form a continuous grading effect of particle size. Its compressive and flexural strengths are only similar to those of Comparative Example 6, and its mechanical properties are poor. Due to the absence of iron-based amorphous alloy particles, only conductive fibers cannot form a good electron channel, and its thermoelectric properties are also poor. Alkaline substances are still present in the XRD spectrum, and the alkali reversion phenomenon cannot be effectively suppressed.
[0105] The microstructure of the cement-based composite material obtained from Comparative Example 9 ( Fig.12 ) It can be seen that a large number of deep tunnel holes appear in local areas of the material. This is mainly because the cement-based composite material contains only silica sand, a fine aggregate, and does not contain oyster shell particles and iron-based amorphous alloy particles, which makes the void ratio between cement stone and silica sand large, and the contact area between aggregate and calcium aluminate cement is insufficient. During the mixing process, harmful pores are formed in the fresh cement, affecting its density, which will reduce its strength performance. The microscopic morphology of the cement-based composite material obtained in Example 8 ( Fig.13 ) It can be seen that the composite material does not have large pore structures, and the microscopic morphology is better than Fig.12 It is denser because the particle size of silica sand is 0.2mm~3.35mm, the particle size of oyster shell particles is 60~500μm, and the particle size of iron-based amorphous alloy powder is 1~80μm. The combination of the three forms a good particle size continuous grading effect, which can fully fill the pores of the concrete system, reduce the porosity of the concrete, and improve its density, thereby improving the strength of the cement-based composite material.
[0106] The effect test of oyster shell particles in cement-based composite materials: 5g of oyster shell particles were placed in 200mL of cement colloid pore simulation liquid. The simulated cement colloidal pore liquid was 10 parts of saturated Ca(OH)2 solution, 1 part of aluminum sol, and 1 part of silica sol. The pH value of the simulated concrete pore liquid was adjusted with 0.8mol / L NaHCO3 solution. The pH value of the solution changed with the immersion time as shown in the following figure. Fig.14 As shown, the results showed that the pH value of oyster shell particles decreased to 8.3 after being immersed in the cement mastic pore simulation liquid for 28 days.
[0107] The calcium aluminate cement-based material before adding oyster shell particles, that is, the calcium aluminate cement-based material obtained in Comparative Example 6, was placed in a curing box at 20°C and a relative humidity not equal to 90% for 28 days, and then part of the powder was taken for XRD detection. The results are as follows: Fig.10 As shown in (a), the calcium aluminate cement-based material after adding oyster shell particles, that is, the calcium aluminate cement-based composite material obtained in Comparative Example 4, was subjected to XRD detection. Fig.10 As shown in (b), the XRD results show Fig.10 The phase types of (a) and (b) are basically the same, mainly composed of CSH(Ⅰ), CSH(Ⅱ) and xCaO·ySiO2·zAl2O3·mH2O and alkaline substances Ca2Al2SiO6(OH)2 and Ca2(SiO3)(OH)2. However, before adding oyster shell particles, the diffraction angles corresponding to the alkaline substance Ca2Al2SiO6(OH)2 in the cement colloid were 32.018°, 61.209° and 65.133° at 2θ respectively; after adding oyster shell particles, Ca2Al2SiO6(OH)2 had only a weak peak at 61.209°, indicating that oyster shell particles can reduce the content of alkaline substance Ca2Al2SiO6(OH)2 in cement colloid. Another alkaline Ca2(SiO3)(OH)2 phase Fig.10 There are also three diffraction peaks in (a), whose 2θ are 29.855°, 37.489° and 71.059° respectively; Fig.10 (b) also has only a weak diffraction peak at 2θ=37.489°. Therefore, oyster shell particles can inhibit the formation of Ca2Al2SiO6(OH)2 and Ca2(SiO3)(OH)2 to a certain extent. Oyster shell particles have a certain effect on the inhibition of alkali reversion, but the existence of Ca2Al2SiO6(OH)2 and Ca2(SiO3)(OH)2 alkaline phases indicates that their single action has limited effect on the inhibition of alkali reversion.
[0108] Effect test of iron-based amorphous alloy in cement-based composite materials: amorphous iron and crystalline iron-based alloys of the same composition were placed in a concrete simulation liquid with a pH value of 12. The simulated concrete pore liquid was 10 parts of saturated Ca(OH)2 solution, 1 part of aluminum sol, and 1 part of silica sol. The pH value of the simulated concrete pore liquid was adjusted with 0.8 mol / L NaHCO3 solution. 1g of amorphous Fe was placed in 200mL of saturated Ca(OH)2 solution. The pH value of the solution was tested with a pH meter after 7 and 14 days. The results are as follows: Fig.15 As shown in the figure, the pH value of amorphous iron is reduced to 10.6 after 7 days of immersion in saturated Ca(OH)2 solution, and the pH value is reduced to 7.6 after 14 days. The reason is that amorphous iron, as a metallic glass, has a higher Gibbs free energy during oxidation due to its long-range disordered atomic structure and thermodynamic non-equilibrium state, and is more likely to produce the following chemical reactions:
[0109] Fe-2e→Fe 2+ (1)
[0110] Fe 2+ +H2O→FeOH + +H + (2)
[0111] therefore Fig.15 The results show that amorphous iron can effectively reduce the pH value of concrete simulation fluid.
[0112] The calcium aluminate cement-based material before adding the iron-based amorphous alloy powder, i.e. the calcium aluminate cement-based composite material obtained in Comparative Example 6, was subjected to XRD detection. Fig.10 As shown in (a), the calcium aluminate cement-based material after adding the iron-based amorphous alloy powder, that is, the calcium aluminate cement-based composite material obtained in Comparative Example 7, is subjected to XRD detection. Fig.10 (c) As shown in Figure 2, the XRD results show that Fig.10 (c) shows that Ca2Al2SiO6(OH)2 has only two weak peaks, and Ca2(SiO3)(OH)2 also has only two diffraction peaks. Fig.10 (a) Compared with the above, the number and intensity of diffraction peaks are decreased, indicating that the iron-based amorphous alloy can inhibit the precipitation of these two alkaline substances to a certain extent.
[0113] The Fe-based amorphous alloy and the Fe-based crystalline alloy were placed in saturated Ca(OH)2 solution, and the polarization curves were measured by the IM6 electrochemical workstation three-electrode method to obtain the Evans polarization diagram as shown in the figure. Fig.16As shown in the figure, the open circuit potential Ea of the Fe-based amorphous alloy is 0.986 V (relative to the standard electrode potential of mercuric oxide, the same below), while the open circuit potential Ea of the Fe-based crystalline alloy is -0.940 V. According to △G=-n(Ec-Ea)F, it shows that the Gibbs free energy △G of the oxidation reaction of the Fe-based amorphous alloy is lower, which is easier to promote the reaction Fe-2e→Fe 2+ The Evans oxidation current density was obtained by extrapolation, and the amorphous iron oxidation current density was 0.90395 mA / cm 2 , the crystalline iron oxidation current density is 0.16696mA / cm 2 , indicating that amorphous iron actually loses more electrons when reacting (1) in concrete simulation fluid, that is, it is more active in oxidation reaction than crystalline iron. Both crystalline iron and amorphous iron have certain passivation properties, but amorphous iron releases more electrons during passivation, indicating that amorphous iron can release protons H more efficiently. + Thus, the alkali in cement during the hydration stage is neutralized. The H2O in reaction (2) comes from the water provided externally during the cement curing process. The above experiments prove that the iron-based amorphous alloy has a certain effect on inhibiting the alkali reversion phenomenon, but the existence of the alkaline phases of Ca2Al2SiO6(OH)2 and Ca2(SiO3)(OH)2 shows that their single action has limited effect on inhibiting the alkali reversion phenomenon.
[0114] In addition, by Fig.11 The microscopic morphology and composition of the iron-based amorphous alloy in the cement-based composite material after curing for 28 days show that the color of the outer surface of the iron-based amorphous alloy sphere in contact with the calcium aluminate cement matrix is different from that of the core. The reason is that an oxidation reaction occurs on the outer surface of the iron-based amorphous alloy and a passivation film is formed. The core of the iron-based amorphous alloy contains 87.49% Fe and 3.91% Si, indicating that the core of the iron-based amorphous alloy remains non-oxidized. The addition of iron-based amorphous alloy powder is beneficial to improving the electrical and thermal conductivity of cement-based composite materials.
[0115] The above embodiments are preferred experimental methods of the present invention, but the implementation methods of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A cement-based composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 300-550 parts of calcium aluminate cement powder, 600-1600 parts of silica sand, 45-160 parts of oyster shell particles, 45-160 parts of iron-based amorphous alloy powder, 5-15 parts of conductive basalt fiber and 120-280 parts of water.
2. The cement-based composite material according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 400-500 parts of calcium aluminate cement powder, 900-1500 parts of silica sand, 60-120 parts of oyster shell particles, 60-120 parts of iron-based amorphous alloy powder, 8-12 parts of conductive basalt fiber and 140-250 parts of water.
3. The cement-based composite material according to claim 1, characterized in that: The conductive basalt fiber is a basalt fiber with a metal coating on the surface.
4. The cement-based composite material according to claim 3, characterized in that: The metal plating layer includes silver and / or nickel metal plating layer.
5. The cement-based composite material according to claim 1, characterized in that: The alloy of the iron-based amorphous alloy powder is selected from one or more of amorphous Fe-Si-B alloy, amorphous Fe-B alloy, amorphous Fe-BC alloy, amorphous Fe-Si-BC alloy, and amorphous Fe-Co-Si-B alloy.
6. The cement-based composite material according to claim 1, characterized in that: The particle size of the oyster shell particles is 60 to 500 μm.
7. The cement-based composite material according to claim 1, characterized in that: The preparation method of the conductive basalt fiber comprises the following steps: S1. Place the basalt fiber in the pretreatment solution and perform ultrasonic vibration for 20 to 30 minutes; S2. placing the basalt fiber obtained in step S1 in a chemical plating solution for surface chemical metal plating for 10 to 20 minutes.
8. The cement-based composite material according to claim 1, characterized in that: The chemical components of the calcium aluminate cement powder include calcium aluminate, calcium aluminosilicate, calcium silicate and silicon dioxide.
9. A method for preparing the cement-based composite material according to any one of claims 1 to 8, comprising the following steps: mixing water and calcium aluminate cement powder, then adding silica sand, oyster shell particles, iron-based amorphous alloy powder, and conductive basalt fiber and stirring to form mortar, placing the mortar in a mold and vibrating it on a concrete vibration table to obtain the cement-based composite material.
10. Use of the cement-based composite material according to any one of claims 1 to 8 in the preparation of thermal insulation building materials and / or thermoelectric conversion device materials.
Citation Information
Cited By
Ground source heat pump EICP mortar backfill material and preparation method and application thereof
CN122426971A